Pemanfaatan Jerami Padi Sebagai Bahan Baku Pembuatan Kertas Ramah Lingkungan Di SMK Dan SMA Lubuk Basung - Arziyah, Dewi; Mutiar, Sri; Anggia, Malse; Wijayanti, Ruri; Yusmita, Lisa; Ariyetti, Ariyetti (LPPM Universitas Dharma Andalas, 2025)
Rice is the largest agricultural commodity in West Sumatra. It has an impact on the abundance of rice straw waste. Rice straw consists of 37.7% cellulose, 22.0% hemicellulose and 16.6% lignin. With its high cellulose content, rice straw has the potential to be utilised as a raw material for papermaking. On the other hand, small-scale cardboard industries that use raw materials from the pulp/paper industry's organic solid waste (sludge) are currently experiencing difficulties in the continuity of supply of other fibre materials as a mixture of organic solid waste, so processing rice straw into pulp through the kraft process with NaOH chemicals is expected to be an alternative raw material for the paper industry. In addition, the utilisation of rice straw into paper is also expected to reduce the waste produced. The service activity aims to provide information and training on making paper from rice straw to students at the secondary school level. From the activities, students were very enthusiastic in practicing paper making and making crafts from rice stalks.